2012
DOI: 10.1103/physrevb.85.054505
|View full text |Cite
|
Sign up to set email alerts
|

s-wave superconductivity with orbital-dependent sign change in checkerboard models of iron-based superconductors

Abstract: We study three different multi-orbital models for iron-based superconductors (iron-SCs) in the solvable limit of weakly coupled square plaquettes. The strongest superconducting (SC) pairing is in the A1g s-wave channel and its development is correlated with the emergence of the next-nearestneighbour antiferromagnetism (NNN-AFM). For the models with more than three orbitals, this study suggests that the signs of the intra-orbital pairing order parameters of the dxy and the dxz (or dyz) orbitals must be opposite… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
(69 reference statements)
0
33
1
Order By: Relevance
“…It is, however, different from the result in the very-strong-coupling limit in Ref. [57], where the strong interorbital repulsion favors different signs between the d xy intraorbital and the d xz; d yz intraorbital pairings. Some quantitative differences between Figs.…”
Section: Mean-field Analysiscontrasting
confidence: 44%
“…It is, however, different from the result in the very-strong-coupling limit in Ref. [57], where the strong interorbital repulsion favors different signs between the d xy intraorbital and the d xz; d yz intraorbital pairings. Some quantitative differences between Figs.…”
Section: Mean-field Analysiscontrasting
confidence: 44%
“…In contrast, in a multiorbital model, many theoretical calculations based on weak-coupling approaches have shown that the gap functions are very sensitive to detailed band structures and vary significantly when the doping changes [6,[24][25][26][27][28]. The robustness of the form factor has therefore been argued to favor strong-coupling approaches, which emphasize electron-electron correlation or the effective next-nearest-neighbor (NNN) antiferromagnetic (AF) exchange coupling J 2 [29][30][31][32][33][34][35] as a primary source of the pairing force. However, realistically, it is very difficult to imagine that such a local exchange interaction remains identical between all d-orbital electrons if a multiple-d-orbital model is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The disappearance of hole pockets at the point yields the exclusion of s ± wave for the SC symmetry, because the nesting vector is modified from ( , 0) (unfolded Brillouin zone notation in this section). The nodeless d wave and nodal d wave have been proposed by a nesting scenario [11][12][13][14][15], while the robustness of s-wave has been pointed out by a strong-coupling scenario taking into account the next-nearest neighbor exchange interaction [16][17][18]. On the other hand, an s ++ wave mediated by the orbital fluctuations is another candidate [14].…”
Section: Spin Fluctuations and Superconducting Symmetry In A X Fe 2−ymentioning
confidence: 99%
“…Such variety in materials is a characteristic of Fe-based superconductors. Their superconductivity mechanism is still controversial; the spin-fluctuation scenario yields s ± symmetry in most of Fe-based superconductors [7][8][9][10]; however, for instance in K x Fe 2−y Se 2 , different superconducting (SC) symmetries have been proposed by different theoretical approaches [11][12][13][14][15][16][17][18]. On the other hand, the orbital-fluctuation scenario gives s ++ symmetry [19,20].…”
Section: Introductionmentioning
confidence: 99%